Diagnostic ultrasound enhances, then reduces, exogenously induced brain activity of mice - Tan, Henry; Griggs, Devon J.; Chen, Lucas; Culevski, Kahte Adele; Floerchinger, Kathryn; Phutirat, Alissa; Koh, Gabe; Schimek, Nels; Mourad, Pierre D. (Frontiers in Human Neuroscience, 2025)
Transcranially delivered diagnostic ultrasound (tDUS) applied to the human brain can modulate those brains such that they became more receptive to external stimulation relative to sham ultrasound exposure. Here, we sought to directly measure the effect of tDUS on mouse brain activity subjected to an external stimulation—a blinking light. Using electrocorticography, we observed a substantial increase in median brain activity due to tDUS plus a blinking light relative to baseline and relative to sham tDUS plus a blinking light. Subsequent brain activity decreased after cessation of tDUS but with continuation of the blinking light, though it remained above that demonstrated by mice exposed to only a blinking light. In a separate experiment, we showed that tDUS alone, without a blinking light, had no observable effect on median brain activity, but upon its cessation, brain activity decreased. These results demonstrate that simultaneous exposure to tDUS and blinking light can increase the receptivity of the visual cortex of mice exposed to that light, and that prior exposure to tDUS can reduce subsequent brain activity. In each case, these results are consistent with published data. Our results on mice echo published human results but do not directly explain them, since their test subjects received less intense diagnostic ultrasound than did our mice. Given the near ubiquity of diagnostic ultrasound systems, further progress along this line of research could one day lead to the widespread use of diagnostic ultrasound to intentionally modulate human brain function during exogenous stimulation.